Abuse, nocturnal stress hormones, and coronary heart disease risk among women with HIV. Issue 5 (4th May 2017) - Dale, Sannisha K.; Weber, Kathleen M.; Cohen, Mardge H.; Brody, Leslie R.
ABSTRACT: This study investigated the relationships among abuse, nocturnal levels of cortisol and norepinephrine (NE), and coronary heart disease (CHD) risk as measured by the Framingham risk score among women with human immunodeficiency virus (HIV). Participants ( n  = 53) from the Chicago Women's Interagency HIV Study (WIHS), a longitudinal prospective cohort study initiated in 1994, were enrolled in this study during 2012. At WIHS baseline and annual follow-up visits, women were asked about recent experiences of abuse. Summary variables captured the proportion of visits for which women reported recent (past 12 months) physical, sexual, and domestic abuse. Cortisol and NE were assayed in overnight urine samples and adjusted for creatinine levels. Recent abuse was not significantly associated with levels of cortisol, NE, or NE/cortisol ratio. However, higher NE/cortisol ratio was significantly related to higher CHD risk score, higher cortisol was significantly related to lower CHD risk score, and NE was not associated with CHD risk score. In addition, higher proportions of visits with recent sexual abuse, physical abuse, and domestic abuse were significantly related to higher CHD risk score. The association between abuse exposure and CHD risk in the context of HIV infection is likely complex and may involve dysregulation of multiple neurobiological systems. Future research is needed to better understand these relationships and prevention and intervention efforts are needed to address abuse among women with HIV.